# Class 12 RD Sharma Solutions – Chapter 17 Increasing and Decreasing Functions – Exercise 17.2 | Set 2

### Question 11. Show that f(x) = cos^{2} x is a decreasing function on (0, π/2).

**Solution:**

We have,

f(x) = cos

^{2}xOn differentiating both sides with respect to x, we get

f'(x) =

f'(x) = 2 cos x (– sin x)

f'(x) = – sin 2x

Now for 0 < x < π/2,

=> sin 2x > 0

=> – sin 2x < 0

=> f'(x) < 0

Thus, f(x) is decreasing on x ∈ (0, π/2).

Hence proved.

### Question 12. Show that f(x) = sin x is an increasing function on (–π/2, π/2).

**Solution:**

We have,

f(x) = sin x

On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = cos x

Now for –π/2 < x < π/2,

=> cos x > 0

=> f'(x) > 0

Thus, f(x) is increasing on x ∈ (–π/2, π/2).

Hence proved.

### Question 13. Show that f(x) = cos x is a decreasing function on (0, π), increasing in (–π, 0) and neither increasing nor decreasing in (–π, π).

**Solution:**

We have,

f(x) = cos x

On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = – sin x

Now for 0 < x < π,

=> sin x > 0

=> – sin x < 0

=> f’(x) < 0

And for –π < x < 0,

=> sin x < 0

=> – sin x > 0

=> f’(x) > 0

Therefore, f(x) is decreasing in (0, π) and increasing in (–π, 0).

Hence f(x) is neither increasing nor decreasing in (–π, π).

Hence proved.

### Question 14. Show that f(x) = tan x is an increasing function on (–π/2, π/2).

**Solution:**

We have,

f(x) = tan x

On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = sec

^{2}xNow for –π/2 < x < π/2,

=> sec

^{2 }x > 0=> f’(x) > 0

Thus, f(x) is increasing on interval (–π/2, π/2).

Hence proved.

### Question 15. Show that f(x) = tan^{–1} (sin x + cos x) is a decreasing function on the interval (π/4, π /2).

**Solution:**

We have,

f(x) = tan

^{–1}(sin x + cos x)On differentiating both sides with respect to x, we get

f'(x) =

f'(x) =

f'(x) =

f'(x) =

f'(x) =

f'(x) =

f'(x) =

Now for π/4 < x < π/2,

=> < 0

=> f’(x) < 0

Thus, f(x) is decreasing on interval (π/4, π/2).

Hence proved.

### Question 16. Show that the function f(x) = sin (2x + π/4) is decreasing on (3π/8, 5π/8).

**Solution:**

We have,

f(x) = sin (2x + π/4)

On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = 2 cos (2x + π/4)

Now we have, 3π/8 < x < 5π/8

=> 3π/4 < 2x < 5π/4

=> 3π/4 + π/4 < 2x + π/4 < 5π/4 + π/4

=> π < 2x + π/4 + 3π/2

As, 2x + π/4 lies in 3rd quadrant, we get,

=> cos (2x + π/4) < 0

=> 2 cos (2x + π/4) < 0

=> f'(x) < 0

Thus, f(x) is decreasing on interval (3π/8, 5π/8).

Hence proved.

### Question 17. Show that the function f(x) = cot^{–1} (sin x + cos x) is increasing on (0, π/4) and decreasing on (π/4, π/2).

**Solution:**

We have,

f(x) = cot

^{–1}(sin x + cos x)On differentiating both sides with respect to x, we get

f'(x) =

f'(x) =

f'(x) =

f'(x) =

f'(x) =

f'(x) =

f'(x) =

Now for π/4 < x < π/2,

=> < 0

=> cos x – sin x < 0

=> f’(x) < 0

Also for 0 < x < π/4,

=> > 0

=> cos x – sin x > 0

=> f'(x) > 0

Thus, f(x) is increasing on interval (0, π/4) and decreasing on intervals (π/4, π/2).

Hence proved.

### Question 18. Show that f(x) = (x – 1) e^{x} + 1 is an increasing function for all x > 0.

**Solution:**

We have,

f(x) = (x – 1) e

^{x}+ 1On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = e

^{x}+ (x – 1) e^{x}f'(x) = e

^{x}(1+ x – 1)f'(x) = x e

^{x}Now for x > 0,

⇒ e

^{x}> 0⇒ x e

^{x}> 0⇒ f’(x) > 0

Thus f(x) is increasing on interval x > 0.

Hence proved.

### Question 19. Show that the function x^{2} – x + 1 is neither increasing nor decreasing on (0, 1).

**Solution:**

We have,

f(x) = x

^{2}– x + 1On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = 2x – 1 + 0

f'(x) = 2x – 1

Now for 0 < x < 1/2, we have

=> 2x – 1 < 0

=> f(x) < 0

Also for 1/2 < x < 1,

=> 2x – 1 > 0

=> f(x) > 0

Thus f(x) is increasing on interval (1/2, 1) and decreasing on interval (0, 1/2).

Hence, the function is neither increasing nor decreasing on (0, 1).

Hence proved.

### Question 20. Show that f(x) = x^{9} + 4x^{7} + 11 is an increasing function for all x ∈ R.

**Solution:**

We have,

f(x) = x

^{9}+ 4x^{7}+ 11On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = 9x

^{8}+ 28x^{6}+ 0f'(x) = 9x

^{8}+ 28x^{6}f'(x) = x

^{6}(9x^{2}+ 28)As it is given, x ∈ R, we get,

=> x

^{6}> 0Also, we can conclude that,

=> 9x

^{2}+ 28 > 0This gives us, f'(x) > 0.

Hence, the function is increasing on the interval x ∈ R.

Hence proved.

### Question 21. Show that f(x) = x^{3} – 6x^{2} + 12x – 18 is increasing on R.

**Solution:**

We have,

f(x) = x

^{3}– 6x^{2}+ 12x – 18On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = 3x

^{2}– 12x + 12 – 0f'(x) = 3x

^{2}– 12x + 12f'(x) = 3 (x

^{2}– 4x + 4)f'(x) = 3 (x – 2)

^{2}Now for x ∈ R, we get,

=> (x – 2)

^{2}> 0=> 3 (x – 2)

^{2}> 0=> f'(x) > 0

Hence, the function is increasing on the interval x ∈ R.

Hence proved.

### Question 22. State when a function f(x) is said to be increasing on an interval [a, b]. Test whether the function f(x) = x^{2} – 6x + 3 is increasing on the interval [4, 6].

**Solution:**

A function f(x) is said to be increasing on an interval [a, b] if f(x) > 0.

We have,

f(x) = x

^{2}– 6x + 3On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = 2x – 6 + 0

f'(x) = 2x – 6

f'(x) = 2(x – 3)

Now for x ∈ [4, 6], we get,

=> 4 ≤ x ≤ 6

=> 1 ≤ (x – 3) ≤ 3

=> x – 3 > 0

=> f'(x) > 0

Thus, the function is increasing on the interval [4, 6].

Hence proved.

### Question 23. Show that f(x) = sin x – cos x is an increasing function on (–π/4, π/4).

**Solution:**

We have,

f(x) = sin x – cos x

On differentiating both sides with respect to x, we get

f'(x) =

f'(x) = cos x + sin x

f'(x) =

f'(x) =

f'(x) =

Now we have, x ∈ (–π/4, π/4)

=> –π/4 < x < π/4

=> 0 < (x + π/4) < π/2

=> sin 0 < sin (x + π/4) < sin π/2

=> 0 < sin (x + π/4) < 1

=> sin (x + π/4) > 0

=> √2 sin (x + π/4) > 0

=> f'(x) > 0

Thus, the function is increasing on the interval (–π/4, π/4).

Hence proved.

### Question 24. Show that f(x) = tan^{–1} x – x is a decreasing function on R.

**Solution:**

We have,

f(x) = tan

^{–1}x – xOn differentiating both sides with respect to x, we get

f'(x) =

f'(x) =

f'(x) =

f'(x) =

Now for x ∈ R, we have,

=> x

^{2}> 0 and 1 + x^{2}> 0=> > 0

=> < 0

=> f'(x) < 0

Thus, f(x) is a decreasing function on the interval x ∈ R.

Hence proved.

### Question 25. Determine whether f(x) = –x/2 + sin x is increasing or decreasing function on (–π/3, π/3).

**Solution:**

We have,

f(x) = –x/2 + sin x

On differentiating both sides with respect to x, we get

f'(x) =

f'(x) =

Now, we have

=> x ∈ (–π/3, π/3)

=> –π/3 < x < π/3

=> cos (–π/3) < cos x < cos (π/3)

=> 1/2 < cos x < 1/2

=> > 0

=> f'(x) > 0

Thus, f(x) is a increasing function on the interval x ∈ (–π/3, π/3).

Hence proved.

## Please

Loginto comment...